Hubungan Berpikir Positif dengan Kecemasan Berbicara di Depan Umum pada Mahasiswa Semester Akhir - Fidiah Nur Pratiwi; Niken Titi Pratitis; Rahma Kusumandari (Journal of Health, Medical, and Psychological Studies, 2025)
Public speaking anxiety remains a persistent psychological challenge among final-year university students, particularly in academic contexts that demand frequent oral presentations and evaluative communication. This field-based quantitative study examines the relationship between positive thinking and public speaking anxiety among undergraduate students in their final semester. Using a correlational research design, data were collected from 366 students selected through accidental sampling across six faculties at Universitas 17 Agustus 1945 Surabaya. Positive thinking and public speaking anxiety were measured using validated Likert-type scales with satisfactory psychometric properties. Preliminary assumption testing indicated non-normal and non-linear data distribution, leading to the application of Spearman’s rho correlation analysis. The findings reveal a significant negative relationship between positive thinking and public speaking anxiety, indicating that students who demonstrate higher levels of constructive cognitive orientation tend to experience lower anxiety when speaking in public settings. These results highlight the central role of cognitive processes in shaping emotional responses to communication demands. The study contributes theoretically by reinforcing cognitive-based models of communication anxiety and practically by informing the design of psychological and educational interventions aimed at strengthening positive thinking to reduce public speaking anxiety among university students.